Distribution of Acanthephyra brevicarinata Hanamura, 1984 and A. brevirostris Smith, 1885 (Crustacea: Decapoda: Caridea: Acanthephyridae), in Pacific Mexico - Hendrickx, Michel E.; Ríos-Elósegui, Daniela (Zootaxa, 2014)
Two species of the Acanthephyridae, Acanthephyra brevicarinata Hanamura, 1984, and A. brevirostris Smith, 1885, are reported for the Pacific coast of Mexico. The number of known localities for A. brevicarinata, a species endemic to the eastern Pacific, is increased from 24 to 70 and the number of specimens on records from 160 to 363. New distribution limits are provided for this species, from 25°02’N; 112°54’W to 16°58’N; 100°55’W, including the central and northern Gulf of California from 28°01’N; 112°17’W southwards. Based on previous information related to its capture and the morphology of its first larval stage, A. brevicarinata is considered to be part of the nektobenthic fauna. New records for A. brevirostris confirm its presence within the Gulf of California.